Cutaneous signs are important in the diagnosis of the rare neoplasia syndrome Carney complex - Vandersteen, Anthony (2009)
We describe a 15-year-old boy who presented with a stroke. Brain MRI imaging showed thalamic and multiple cerebral infarcts. An echocardiogram revealed multiple atrial masses, which were resected. Histological examination confirmed multiple atrial myxomas. Further clinical examination of the patient revealed subtle buccal and peri-oral lentigenes. The diagnosis of Carney complex was made clinically. The patient was subsequently diagnosed with testicular seminomas and a cutaneous angiomyxoma. Genetic investigation revealed a pathological mutation in the PRKAR1A gene. We review the reported manifestations and presentations of Carney complex, along with current diagnostic guidelines. We emphasise the importance of recognising the cutaneous manifestations of this rare autosomal dominantly inherited neoplasia syndrome.